Hyperthyroidism in Takotsubo syndrome: prevalence, clinical features and long-term outcomes. (25th November 2020) - Scudiero, F; Arcari, L; Silverio, A; Citro, R; Bossone, E; Autore, C; Muraca, I; Chinati, P; Sanna, G; Piti, A; Parodi, G
Abstract: Background: Takotsubo syndrome (TTS) is an increasingly recognized form of transient left ventricular dysfunction, often completely reversible. The exact pathogenesis is not fully understood, but central role of adrenergic dysfunction has been widely accepted. A possible link between hyperthyroidism and TTS has been hypothesized, since thyroid and adrenergic systems are in closely connection. Nevertheless, clinical study to define the association between hyperthyroidism and TTS is still lacking. Purpose: This study aimed to assess prevalence, clinical features and long-term outcomes of hyperthyroidism at presentation in TTS patients. Methods: Overall, 590 TTS patients from 23 centers were included in this prospective registry. Thyroid profile was available for 314 patients at time of TTS admission. Patients in hypothyroid state (n=32) according to TSH value were excluded. The remaining 282 patients were divided in normal thyroid state and hyperthyroid state according to TSH value, respectively 240 (85%) and 42 (15%) patients. Results: The median age was 73±10 and the female rate was 93%. TTS related to physical trigger was mostly detected in hyperthyroidism patients (52% vs 30%, respectively in hyperthyroid state and normal thyroid state; p=0.005); while, TTS related to emotional trigger was less common (19%, vs 38%, respectively in hyperthyroid state and normal thyroid state; p=0.016). In TTS unprovoked by a stress factor, there was no statistical difference in thyroid state (29% vs 31%, respectively in hyperthyroid state and normal thyroid state; p=0.690). Follow-up rate was 95% and follow-up length was 41±36 months. At long-term follow-up, mortality rate was 39% and 20% in hyperthyroidism and normal thyroid state, respectively (p=0.008; Figure 1) and adverse event rates (the composite of all-cause death, myocardial infarction and stroke) were 39% and 24% in hyperthyroid state and normal thyroid state, respectively (p=0.034). At multivariable analysis, hyperthyroidism resulted as a strong predictor of mortality (OR 3.82, 95% CI: 1.71–8.50; p=0.001) and of adverse event rates (OR 2.18, 95% CI: 1.19–3.98; p=0.011). Conclusion: Hyperthyroidism at presentation is relatively common in TTS patients and associated with physical triggers and unfavorable long-term prognosis. Funding Acknowledgement: Type of funding source: None